No Biological Evidence of XMRV in Blood or Prostatic Fluid from Prostate Cancer Patients - Mendoza, Ramon (Public Library of Science, 2012)
BACKGROUND: XMRV (xenotropic murine leukemia virus-related virus) was initially discovered in association with prostate cancer and later with chronic fatigue syndrome (CFS). Its association with CFS is now largely discredited, and current results support a laboratory origin for XMRV with no reproducible evidence for infection of humans. However, some results indicating the presence of XMRV in prostate cancer are difficult to attribute to sample contamination. Here we have sought biological evidence that might confirm the presence of XMRV in prostate cancer samples previously having tested positive. METHODS AND RESULTS: We have tested for infectious XMRV and neutralizing antibodies against XMRV in blood plasma from 29 subjects with prostate cancer, and for infectious XMRV in prostate secretions from another five prostate cancer subjects. Nine of these subjects had previously tested positive for XMRV by PCR or by virus assay. We did not detect XMRV or related retroviruses in any sample, and the neutralizing activities of the plasma samples were all very low, a result inconsistent with XMRV infection of the plasma donors. CONCLUSIONS: We find no evidence for XMRV infection of any human subject tested, either by assay for infectious virus or for neutralizing antibodies. Our results are consistent with the majority of published studies on XMRV, which find that XMRV is not present in humans. The observed low to undetectable XMRV neutralization by human plasma indicates a lack of innate restriction of XMRV replication by soluble factors in human blood.